FORMATION OF FINANCIAL LITERACY OF STUDENTS IN MATHEMATICS LESSONS - Mingboyeva Yulduz Boboxolovna (Journals Park Publishing, 2022)
The article discusses the issue of the formation of financial literacy of students of secondary schools. Ways to increase financial literacy are presented.
Keywords: financial literacy, financial knowledge, mathematics, approach, Economics, a contextual issue.